Understanding interferometry for micro-cantilever displacement detection - von Schmidsfeld, Alexander; Nörenberg, Tobias; Temmen, Matthias; Reichling, Michael (Beilstein Journal of Nanotechnology, 2016)
Interferometric displacement detection in a cantilever-based non-contact atomic force microscope (NC-AFM) operated in ultra-high vacuum is demonstrated for the Michelson and Fabry–Pérot modes of operation. Each mode is addressed by appropriately adjusting the distance between the fiber end delivering and collecting light and a highly reflective micro-cantilever, both together forming the interferometric cavity. For a precise measurement of the cantilever displacement, the relative positioning of fiber and cantilever is of critical importance. We describe a systematic approach for accurate alignment as well as the implications of deficient fiber–cantilever configurations. In the Fabry–Pérot regime, the displacement noise spectral density strongly decreases with decreasing distance between the fiber-end and the cantilever, yielding a noise floor of 24 fm/Hz0.5 under optimum conditions.
Keywords: displacement noise spectral density; interferometer; non-contact atomic force microscope (NC-AFM); opto-mechanic effects

(untitled) - Saulson, P. R. (Phys. Rev. D, 1990)

(untitled) - Putman, C. A. J.; de Grooth, B. G.; van Hulst, N. F.; Greve, J. (Ultramicroscopy, 1992)

(untitled) - Boucher, R.; Villeneuve, B.; Breton, M.; Tetu, M. (IEEE Photonics Technol. Lett., 1992)

(untitled) - Stone, J.; Stulz, L. W. (Electron. Lett., 1987)

Fabry–Perot Interferometers - Hernandez, G. (Cambridge University Press, 1986)

(untitled) - Shyu, L.-H.; Chang, C.-P.; Wang, Y.-C. (Rev. Sci. Instrum., 2011)

(untitled) - Kracke, B.; Damaschke, B. (Rev. Sci. Instrum., 1996)

(untitled) - von Schmidsfeld, A.; Reichling, M. (Appl. Phys. Lett., 2015)

(untitled) - Kippenberg, T. J.; Vahala, K. J. (Science, 2008)

(untitled) - Braginsky, V. B.; Strigin, S. E.; Vyatchanin, S. P. (Phys. Lett. A, 2001)

(untitled) - Kippenberg, T. J.; Rokhsari, H.; Carmon, T.; Scherer, A.; Vahala, K. J. (Phys. Rev. Lett., 2005)

Aufbau eines Tieftemperatur-Rasterkraftmikroskopes - Troeger, L. (Sierke Verlag, 2009)

(untitled) - Moser, A.; Hug, H. J.; Jung, T.; Schwarz, U. D.; Güntherodt, H.-J. (Meas. Sci. Technol., 1993)

(untitled) - Lübbe, J.; Temmen, M.; Rahe, P.; Kühnle, A.; Reichling, M. (Beilstein J. Nanotechnol., 2013)

(untitled) - Lübbe, J.; Temmen, M.; Rode, S.; Rahe, P.; Kühnle, A.; Reichling, M. (Beilstein J. Nanotechnol., 2013)

(untitled) - Lübbe, J.; Tröger, L.; Torbrügge, S.; Bechstein, R.; Richter, C.; Kühnle, A.; Reichling, M. (Meas. Sci. Technol., 2010)

(untitled) - Rugar, D.; Mamin, H. J.; Guethner, P. (Appl. Phys. Lett., 1989)

(untitled) - Albrecht, T. R.; Grütter, P.; Horne, D.; Rugar, D. (J. Appl. Phys., 1991)

(untitled) - Stowe, T. D.; Yasumura, K.; Kenny, T. W.; Botkin, D.; Wago, K.; Rugar, D. (Appl. Phys. Lett., 1997)

(untitled) - Hug, H. J.; Stiefel, B.; van Schendel, P. J. A.; Moser, A.; Martin, S.; Güntherodt, H.-J. (Rev. Sci. Instrum., 1999)

(untitled) - Hoogenboom, B. W.; Frederix, P. L. T. M.; Yang, J. L.; Martin, S.; Pellmont, Y.; Steinacher, M.; Zäch, S.; Langenbach, E.; Heimbeck, H.-J.; Engel, A.; Hug, H. J. (Appl. Phys. Lett., 2005)

(untitled) - Oral, A.; Grimble, R. A.; Özer, H. Ö.; Pethica, J. B. (Rev. Sci. Instrum., 2003)

(untitled) - Rugar, D.; Mamin, H. J.; Erlandsson, R.; Stern, J. E.; Terris, B. D. (Rev. Sci. Instrum., 1988)

(untitled) - Morita, K.; Sugimoto, Y.; Sasagawa, Y.; Abe, M.; Morita, S. (Nanotechnology, 2010)

(untitled) - Albrecht, T. R.; Grütter, P.; Rugar, D.; Smith, D. P. E. (Ultramicroscopy, 1992)

(untitled) - Metzger, C. H.; Karrai, K. (Nature, 2004)

(untitled) - Allers, W.; Schwarz, A.; Schwarz, U. D.; Wiesendanger, R. (Rev. Sci. Instrum., 1998)

(untitled) - Schwarz, A.; Schwarz, U. D.; Langkat, S.; Hölscher, H.; Allers, W.; Wiesendanger, R. (Appl. Surf. Sci., 2002)

(untitled) - Hogenboom, B. W.; Frederix, P. L. T. M.; Fotaidis, D.; Hug, H. J.; Engel, A. (Nanotechnology, 2008)

(untitled) - Patil, S.; Matei, G.; Dong, H.; Hoffmann, P. M.; Karaköse, M.; Oral, A. (Rev. Sci. Instrum., 2005)

(untitled) - Karci, O.; Dede, M.; Oral, A. (Rev. Sci. Instrum., 2014)

(untitled) - Hölscher, H.; Milde, P.; Zerweck, U.; Eng, L. M.; Hoffmann, R. (Appl. Phys. Lett., 2009)

(untitled) - Vogel, M.; Mooser, C.; Karrai, K.; Warburton, R. J. (Appl. Phys. Lett., 2003)